PENDEKATAN PEMBELAJARAN DIFERENSIASI DALAM MENINGKATKAN KETERAMPILAN PROSES SISWA MELALUI PEMBELAJARAN INKUIRI - Henita; Udin Syaefudin Sa’ud; Atep Sujana; Sahroni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This reseach aims to analyze the impact of differentiated learning approach in inquiry learning model on students' process skills in science subjects. The research was conducted qualitatively on October 14, 2024 at SMP Negeri 2 Ciwidey, Kabupaten Bandung. The research sample was taken from one of the 9th grade classes using purposive sampling technique. The results showed that the implementation of inquiry learning integrated with differentiated learning approach was very good, with reaching 97% for teacher activities and 95% for student activities. Teachers were able to implement learning optimally, and students actively participated in the learning process. The observation of students' process skills showed a percentage of 90%, including in the excellent category. This finding shows that the differentiated learning approach in inquiry learning is able to improve students' process skills. The differentiated learning approach through inquiry learning proved effective in accommodating students' diverse learning needs and improving students' process skills.